Analysis of Consumer Data on Black Friday Sales Using Apriori Algorithm - Maharjan, Menuka (SCITECH Nepal, 2019)
Ability to recognize and track patterns in data help businesses shift through the layers of seemingly unrelated data for meaningful relationships. Through this analysis it becomes easy for the online retailers to determine the dimensions that influence the uptake of online shopping and plan effective marketing strategies. This paper builds a roadmap for analyzing consumer’s online buying behavior with the help of Apriori algorithm. The major factors that affect the consumer’s online buying behavior are convenience, ease of use and perceived benefits. Security is also a major consideration when opting to conduct shopping activities online. This study will helping further analyzing the consumer online buying behavior towards Online shopping which will help the retailers to design appropriate marketing strategies for selling their products online which will further help in development of the country.